Studi Penggunaan Statistika dalam Karya Ilmiah Mahasiswa Strata 1 (S-1) STIE Swadaya Jakarta - Bainar, Bainar (Makara Human Behavior Studies in Asia, 2004)
The finally of day, used the Statistic in social and economics research was be important to description of social and economics phenomena’s. How far used intensity of statistics as tools of analysis, the mistake in applied and relevancy with numeric of graduate of statistics and Value of Average Quality at Student of High School of Economic Swadaya in Jakarta is the interesting research. The result of this research are; The low intensity of used statistics analysis in their research, and there is trend that to be complex of used statistic analysis, to be high of the mistake in used them. The lower of ability to understanding the statistical science and others is correlated by the result of this research.